Rise of the e-Nurse: the power of social media in nursing. Issue 2 (4th May 2019) - Ross, Paul; Cross, Rachel
Abstract : The internet and social media have changed the way society communicates, requiring the nursing workforce to develop effective digital literacy skills and attain levels of e-professionalism. The internet provides a unique environment that both connects and disrupts with powerful and unpredictable consequences for healthcare. A networked nursing workforce can influence and create collaborative communities of practice that will develop and shape healthcare. Nurse education must engage with technology and social media to provide a future-ready workforce capable of delivering future eHealth reforms.